2015
DOI: 10.1007/s10072-015-2231-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a simple method for atrial fibrillation screening in patients with stroke

Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia in adult and old people and represents a risk factor for stroke. Correct AF individuation bears strong relevance in primary and secondary stroke prevention. Our goal was to evaluate the reliability of a low-cost, non-invasive technology in detecting AF in acute stroke patients. AFib model BP3MQ1-2D (Microlife USA, Dunedin, FL) showed good accuracy in diagnosing AF in a general cardiologic outpatient population. We carried out an observational study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…The specificity of an AF detection algorithm of home BP monitor values was 80% to 90% in earlier studies, and false‐positive readings were observed. In the present study, the accuracy of IHD at IPP20 was 100% in three measurements.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The specificity of an AF detection algorithm of home BP monitor values was 80% to 90% in earlier studies, and false‐positive readings were observed. In the present study, the accuracy of IHD at IPP20 was 100% in three measurements.…”
Section: Discussionmentioning
confidence: 89%
“…After their report, several reports about the detection of paroxysmal AF by home BP monitors have been published. The sensitivity values were near or equal to 100%, but the specificity values were 80% to 90%, and the agreement between pulse rate and heart rate was not examined simultaneously. In the present study, we confirmed the correlation between the interval of the pulse wave and QRS wave, and we evaluated a new algorithm for the detection of AF by a home BP monitor.…”
Section: Introductionmentioning
confidence: 97%
“…The reported sensitivity and specificity were approximately 80-100% and 89-99%, respectively (table 6). 3662637172737475…”
Section: Newer Detection Methodsmentioning
confidence: 99%
“…Several other studies investigated BP monitors with an algorithm similar to the abovementioned modified algorithm and showed similar accuracy in the detection of AF, except one monitor that had a sensitivity of 30% . In general, these BP monitors had higher sensitivity and specificity in the detection of AF.…”
Section: Studies On the Diagnostic Accuracy Of Automated Blood Pressumentioning
confidence: 98%